2015
DOI: 10.1039/c5ra00755k
|View full text |Cite
|
Sign up to set email alerts
|

p-Aminophenol sensor based on tetra-β-[3-(dimethylamine)phenoxy] phthalocyanine cobalt(ii)/multiwalled carbon nanotube hybrid

Abstract: The hybrid tetra-β-[3-(dimethylamine)phenoxy] phthalocyanine cobalt(ii)/multiwalled carbon nanotube was designed and synthesized, which can serve as an efficient catalyst for sensitive p-aminophenol detection due to synergistic effects between phthalocyanine and the carbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The detection limit was determined to be 45 nM for 4-AP on surface of GPE/PtAM. In Table 1, the results of a comparison study of the present work with some different modied electrodes 1,[10][11][12][13][35][36][37] and different chromatography methods, 4,5,9,[38][39][40][41][42] which show acceptable performance according to the tabulated data of this electrode. Furthermore, the interfering effects of other probable coexisting ions such as Ca 2+ , Cl À , Cr 3+ , Cu 2+ , K + , Mg 2+ , Na + , NO 3 À , PO 4 3À , SO 4 2À and Zn 2+ , were investigated and the results showed that the maximum interfering effects for these ions were seen with the determination of 4-AP (5% tolerable molar ratio >100).…”
Section: Linear Range and Detection Limit Oxidation Of 4-apmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection limit was determined to be 45 nM for 4-AP on surface of GPE/PtAM. In Table 1, the results of a comparison study of the present work with some different modied electrodes 1,[10][11][12][13][35][36][37] and different chromatography methods, 4,5,9,[38][39][40][41][42] which show acceptable performance according to the tabulated data of this electrode. Furthermore, the interfering effects of other probable coexisting ions such as Ca 2+ , Cl À , Cr 3+ , Cu 2+ , K + , Mg 2+ , Na + , NO 3 À , PO 4 3À , SO 4 2À and Zn 2+ , were investigated and the results showed that the maximum interfering effects for these ions were seen with the determination of 4-AP (5% tolerable molar ratio >100).…”
Section: Linear Range and Detection Limit Oxidation Of 4-apmentioning
confidence: 99%
“…Different electrodes have been made to identify and measure aminophenol. 1,[10][11][12][13] An agarose is a polysaccharide polymer material, commonly extracted from seaweed (Scheme 1). Agarose, a kind of natural polysaccharide, has been widely used for immobilization of enzymes, antibodies and chemical molecules due to its attractive properties of excellent lm-forming ability, biocompatibility, non-toxicity, high mechanical strength and inexpensiveness.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] However, these techniques require incorporation of materials for better specificity and sensitivity. Over the years, materials including thin pyrolytic carbon films, [17] multi-walled carbon nanotubes, [4,12,[18][19][20] poly (glycine) composite, [12] reduced graphene oxide and poly(3,4ethylenedioxythiophene) nanotubes, [21] bimetallic Pd-Ag/reduced graphene oxide, [22] polypyrrole nanofiber-decorated reduced graphene oxide nanocomposites, [23] cerium dioxide zinc sulphide nanoparticles, [24,25] planar metallophthalocyanines (MPcs), [26][27][28][29][30] dimeric europium double-decker phthalocyanine [31] and thermosensitive polymer(s) [20] have been developed for the electrochemical detection of PA. Dimeric rare-earth doubledecker phthalocyanine is a highly complicated sandwich-type derivative that consists of two europium(III) ions and four phthalocyanines rings as coordinating entities, with two rings joined together through statistical condensation. As an alternative to the use of planar MPcs and the dimeric europium double-decker counterpart, we have designed two simpler rare-earth sandwich-type phthalocyaninato chelates without any bridging ligands or condensation, and thus reducing the πelectron system.…”
Section: Introductionmentioning
confidence: 99%
“…16 These two compounds are well known and widely studied because of their toxicity and serious impact on the metabolic activities and growth of the organism. 17,18…”
Section: Introductionmentioning
confidence: 99%